2020
DOI: 10.3390/s20185217
|View full text |Cite
|
Sign up to set email alerts
|

A Screen-Printed Sensor Coupled with Flow System for Quantitative Determination of a Novel Promising Anticancer Agent Candidate

Abstract: A carbon nanofibers modified screen-printed carbon sensor (SPCE/CNFs) was applied for the determination of a novel promising anticancer agent candidate (ethyl 8-(4-methoxyphenyl)-4-oxo-4,6,7,8-tetrahydroimidazo[2,1-c][1,2,4]triazine-3-carboxylate, EIMTC) using square-wave voltammetry (SWV). It is the first method for the quantitative determination of EIMTC. The modified screen-printed sensor exhibited excellent electrochemical activity in reducing EIMTC. The peak current of EIMTC was found to be linear in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
(32 reference statements)
2
8
0
Order By: Relevance
“…The reduction of each of these azomethine groups (C3=N2, C8a=N1) implies the same number of protons and electrons. On the basis of previous findings [ 29 , 30 , 31 , 32 ], it was proposed that the C=N moiety located at positions 3 and 2 would be exclusively susceptible to the electrochemical reduction under these experimental conditions, leading to a protonated CH–NH group. This proposal may be supported by the proven susceptibility of this azomethine moiety to electrochemical reduction in structures of monocyclic, as well as fused, triazinones with single N–N bonds [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The reduction of each of these azomethine groups (C3=N2, C8a=N1) implies the same number of protons and electrons. On the basis of previous findings [ 29 , 30 , 31 , 32 ], it was proposed that the C=N moiety located at positions 3 and 2 would be exclusively susceptible to the electrochemical reduction under these experimental conditions, leading to a protonated CH–NH group. This proposal may be supported by the proven susceptibility of this azomethine moiety to electrochemical reduction in structures of monocyclic, as well as fused, triazinones with single N–N bonds [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 86%
“…On the basis of previous findings [ 29 , 30 , 31 , 32 ], it was proposed that the C=N moiety located at positions 3 and 2 would be exclusively susceptible to the electrochemical reduction under these experimental conditions, leading to a protonated CH–NH group. This proposal may be supported by the proven susceptibility of this azomethine moiety to electrochemical reduction in structures of monocyclic, as well as fused, triazinones with single N–N bonds [ 29 , 30 , 31 ]. In addition, this may be supported by the experimentally observed reduction peak potential, the value of which is close to that of the same azomethine moiety of the ketimine-type undergoing regioselective electrochemical reduction in a structurally similar triazinone [ 32 ].…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Imidazolidinoannelated triazinylformic acid ethyl esters (1-3) and imidazolidinoannelated triazinylacetic acid methyl esters (4-6) (Figure 1) belong to two important classes of molecules with the prospective antitumour or antinociceptive field of relevance, respectively, whose structures in solution and solid state have been established [1][2][3][4][5][6]. They were designed as functionalised isosteric isomers of azacytosine.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the presence of a certain number of non-polar moieties and a temporarily masked polar group were required. The possibility of using two types of nitrogen-rich heterocyclic esters (1-3 and 4-6) as potential future drugs has previously been extensively studied [1][2][3][4][5][6]. It was found that these two types of compounds reveal a low toxicity in vitro and in vivo [1][2][3]5].…”
Section: Introductionmentioning
confidence: 99%